Current State and Perspectives of Twitter usage in Tourism - Tamara Ćurlin; Vanja Šimičević; Božidar Jaković (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Twitter, as the most popular microblog has unquestionable viral impact. It presents what's going on in the world by users posts and reposts and it's became more than just a social network. Individuals, companies, organisations, even governments use Twitter on daily bases and get different kind of benefits from it. Tourism and hospitality sector use it for market positioning, branding, and as an information exchange system. Role of the social networks in tourism has been widely and thoroughly discussed in literature, although this paper narrows the area of interest and puts focus on Twitter. It represents systematic and comprehensive content analysis of 61 articles from 2009-2018. As number of research publications tripled in last two years, we represent how the role of Twitter in tourism developed from marketing tool to business planning and tourist movement predicting source for data mining and other most prominent methods. Now days, Twitter became central database of e-WOM. This paper brings value for both academy and business, as it shows newest findings and research trends, it also shows useful strategies and implementations which can help companies develop their own business strategies.
Keywords: O00; 330; social media; twitter; research; tourism; data mining; e-WOM